New Occurrence of Seifertite and Stishovite in Chang’E‐5 Regolith - Runlian Pang; Jing Yang; Wei Du; Aicheng Zhang; Shirong Liu; Rui Li (Geophysical Research Letters)
Abstract High‐pressure minerals in impact ejecta quantify shock conditions and provide clues for provenance analysis. The sampling site of Chang’E‐5 may contain distal ejecta, which is critical for constraining the impact events and interpreting the constitution of the target geological units. Here, we report a silica fragment consisting of seifertite, stishovite, α‐cristobalite‐like phase, and silica glass in Chang’E‐5 regolith. Both seifertite and stishovite formed via solid‐state transformation mechanism, in which seifertite formed by transition from α‐cristobalite upon pressure loading whereas stishovite may form from seifertite when postshock temperature was significant during pressure release. The coexistence of seifertite and stishovite suggests that their host rock has experienced a peak shock pressure of 11–40 GPa and records different stages of the impact process. Crater size calculation revealed that the host rock of stishovite and seifertite could have been transported from distant craters, confirming the retention of distal ejecta in Chang’E‐5 landing site.